Enforcing ECOWAS judgments in Nigeria through the common law rule on the enforcement of foreign judgments. (2nd January 2019) - Adigun, Muyiwa
Abstract : The ECOWAS Court was established by the Revised ECOWAS Treaty. By virtue of that treaty, the Court has assumed an existence at the international plane and has delivered a number of judgments. This study therefore examines the enforcement of the judgments of the ECOWAS Court in Nigeria as a Member State. The study finds that Nigeria has not been enforcing the judgments of the Court like other Member States. The study further finds that there are five sources of international law namely: treaties, custom, general principles of law recognised by civilised nations, judicial decisions and the writings of the most qualified publicists and that while Nigerian law has addressed domestic effect of treaties and custom, that of other sources most notably the decisions of international tribunals has not been seriously addressed. The study therefore argues that the common law on the enforcement of foreign judgments can be successfully adapted to give domestic effect to the judgments of the ECOWAS Court as an international tribunal in Nigeria. The study therefore recommends that the Nigerian judiciary should take the gauntlet to make the judgments of the ECOWAS Court effective in Nigeria.